2016
DOI: 10.1016/j.ijrobp.2015.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte-Sparing Effect of Stereotactic Body Radiation Therapy in Patients With Unresectable Pancreatic Cancer

Abstract: Purpose Radiation-induced lymphopenia (RIL) is associated with inferior survival in patients with glioblastoma, lung cancer, and pancreatic cancer. We asked whether stereotactic body radiation therapy (SBRT) decreases severity of RIL compared to conventional chemoradiation therapy (CRT) in locally advanced pancreatic cancer (LAPC). Methods and Materials Serial total lymphocyte counts (TLCs) from patients enrolled in a prospective trial of SBRT for LAPC were compared to TLCs from an existing database of LAPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
116
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(135 citation statements)
references
References 34 publications
16
116
2
1
Order By: Relevance
“…This may decrease the potential of systemic progression and improve quality of life 42 . The expanded timing of CRT, however, allows better opportunity to develop and test new radiosensitizing therapeutics that may improve treatment effects 43 . At this time, both SBRT and CRT are valid modalities with different benefits and do not appear in our cohort to independently impact survival.…”
Section: Discussionmentioning
confidence: 99%
“…This may decrease the potential of systemic progression and improve quality of life 42 . The expanded timing of CRT, however, allows better opportunity to develop and test new radiosensitizing therapeutics that may improve treatment effects 43 . At this time, both SBRT and CRT are valid modalities with different benefits and do not appear in our cohort to independently impact survival.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, altered RT fractionation using shorter courses with stereotactic body radiation therapy (SBRT) for pancreatic cancer over 2 weeks has been associated with significantly less radiation-induced lymphopenia than standard chemoradiation therapy (CRT) over 5 weeks[6]. Radiation target volume has also been identified as an important factor with greater treated volumes associated with lower posttreatment lymphocyte counts in non-small cell lung cancer[7].…”
Section: Introductionmentioning
confidence: 99%
“…The increased conformity of proton therapy spares circulating lymphocytes through decreased radiation exposure and fractionation to major blood pools, such as the heart. Other research has shown that lymphopenia and post treatment circulating lymphocyte levels are independent predictors of survival (22,23). These collective findings suggest that proton therapy may improve outcomes through lymphocyte sparing.…”
Section: Editorialmentioning
confidence: 74%